The Relationship Between Family Characteristics and Diet with Nutritional Status in Toddlers Aged 6-59 Months - Elvis Fatima, Tomas (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: Nutrition as a measure of success in fulfilling nutrition for children indicated by the child's weight and height. Food as everything that comes from biological sources and water, both processed and untreated, which is intended as food or drink for human consumption in 2020 stunting was 47.10%, wasting 8.60, underweighing 32.40%. The results of the Timor-Leste Food Nutrition Survey in 2020 Aileu Regency stunting prevalence 53.9%, underweight prevalence 32.2%, wasting prevalence 6.7%. Objective: General Objective to determine the relationship between family characteristics and diet with nutritional status in toddlers aged 6-59 months in the working area of the Lequidoe health center, Lequidoe sub-district, Aileu district in 2022. Method: The method used in the study is a correlational descriptive method with a cross sectional approach, population, the sample in this study is 315 mothers who have children aged 6-59. Result and Discussion: The results showed that there was a significant relationship between maternal knowledge and nutritional status of toddlers with a ?-value of 0.02 (?<0.05). The number of family members there is a significant relationship with the nutritional status of toddlers. ?-value 0.01 (?<0.05). Family income was significantly associated with infant nutritional status ?-value 0.03 (?<0.05). Diet was not significantly associated with nutritional status of toddlers. ?-value 0.0741 (?< 0.05). Feeding frequency There was a significant relationship with the nutritional status of toddlers ?-value 0.00 (?<0.05). Conclusion: according to the results of the study show that there is a significant relationship between variavel knowledge, funding, number of family members, frequency of eating there is a significant relationship with nutritional status toddlers. Variable diet has no relationship with nutritional status, Recommendations to puskesmas as a reference to smooth the process of service to the local community.